Analisis Level Kognitif Soal Programme for International Student Assesment (PISA) Tahun 2018 - Syahrial A; Agus Ramdani; Ahmad Harjono; Aliefman Hakim; Khaerus Syahidi (Kappa Journal, 2022)
This study aims to analyze the PISA science questions released in 2018 to provide an overview for teachers and students in studying them. The method was carried out by describing the cognitive level of the 2018 PISA scientific literacy questions with the subject of this research being the 2018 PISA release science questions on science. The results of the analysis of the 2018 PISA science questions can be concluded in context, level of ability, themes, objectives and variety of questions. The results of the analysis of the 2018 PISA science questions can be concluded in context, level of ability, themes, objectives and variety of questions. The context of understanding the phenomena of science in everyday life and its application in attitude. The cognitive level integrates and concludes from one source, finds the true meaning, analyzes the content and form, finds the true meaning, integrates and concludes from one source, assesses quality and credibility, integrates and concludes from several sources. The theme of the environment, living things, actual phenomena, earth and space. The aim is to increase scientific literacy and be able to apply and practice it in everyday life and a variety of questions in the form of simple multiple choice, complex multiple choice, response and coding, and short answers